2018
DOI: 10.1590/0366-69132018643722463
|View full text |Cite
|
Sign up to set email alerts
|

Effect of doping and sintering in structure and magnetic properties of the diluted magnetic semiconductor ZnO:Ni

Abstract: This work aimed to study a sintered Ni-doped ZnO dilute magnetic semiconductor synthesized by means of a combustion reaction and to evaluate the effect of doping and sintering in the band gap and magnetic properties of the material. X-ray diffraction showed the formation of the ZnO semiconductor phase and also the formation of a second-phase characterized as a solid solution of nickel-zinc oxide. The hysteresis curves showed the success in creating ferromagnetism with doping and the effect of sintering in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…It is known that the pure ZnO has a diamagnetic behavior at room temperature and the extant result (figure 7(a)) is in agreement with that previously reported [34][35][36][37]. Adding some percentage of magnetic materials to non-magnetic compounds produces new composites with different magnetic properties that differ from that of the precursor materials and depend on the additive percentage.…”
Section: Magnetic Propertiessupporting
confidence: 90%
“…It is known that the pure ZnO has a diamagnetic behavior at room temperature and the extant result (figure 7(a)) is in agreement with that previously reported [34][35][36][37]. Adding some percentage of magnetic materials to non-magnetic compounds produces new composites with different magnetic properties that differ from that of the precursor materials and depend on the additive percentage.…”
Section: Magnetic Propertiessupporting
confidence: 90%
“…No additional lines could be formed for the samples of x = 0.00 and 0.025 samples, but as x is increased to and above 0.025, some unidentified lower peaks could be seen at 2θ = 30.96 o for x = 0.05; 2θ = 30.96 o , 55.5 o , 60 o for x = 0.10; and 2θ = 30.96 o , 48.74 o , 55.5 o , 60 o for x = 0.20. This is because the bond energy of Al2O3 is higher than ZnO, and therefore more energy is required for Al ions to enter the ZnO lattice to form the Al-O bond and therefore some of secondary phase could be formed [56][57][58][59]. The lattice parameters a and c, listed in Table 1, are gradually decreased by increasing x.…”
Section: 1-structural Analysismentioning
confidence: 99%
“…It is observed directly that the size comparison from Figures 3a to 3e has a relatively insignificant difference in grain size and has a different level of grain shape homogeneity. The difference in size is due to Ni-doped which has shown that Ni0.08 has the largest grain size, denser structure and fewer defect 32 .…”
Section: Morphological Characterizationmentioning
confidence: 99%